Evidence of thermostable amylolytic activity from Rhizopus microsporus var. rhizopodiformis using wheat bran and corncob as alternative carbon source - Peixoto-Nogueira, S. C.; Sandrim, V. C. [UNESP]; Guimaraes, L. H. S.; Jorge, J.; Terenzi, H. F.; Polizeli, M. L. T. M. (Springer, 2008)
Rhizopus microsporus var. rhizopodiformis produced high levels of alpha-amylase and glucoamylase under solid state fermentation, with several agricultural residues, such as wheat bran, cassava flour, sugar cane bagasse, rice straw, corncob and crushed corncob as carbon sources. These materials were humidified with distilled water, tap water, or saline solutions-Segato Rizzatti (SR), Khanna or Vogel. The best substrate for amylase production was wheat bran with SR saline solution (1:2 v/v). Amylolytic activity was still improved (14.3%) with a mixture of wheat bran, corncob, starch and SR saline solution (1:1:0.3:4.6 w/w/w/v). The optimized culture conditions were initial pH 5, at 45 degrees C during 6 days and relative humidity around 76%. The crude extract exhibited temperature and pH optima around 65 degrees C and 4-5, respectively. Amylase activity was fully stable for 1 h at temperatures up to 75 degrees C, and at pH values between 2.5 and 7.5.
Keywords: glucoamylase; alpha-amylase; thermostable; solid state fermentation; fungi